2016
DOI: 10.1117/1.jmi.3.1.014503
|View full text |Cite
|
Sign up to set email alerts
|

Bolus arrival time and its effect on tissue characterization with dynamic contrast-enhanced magnetic resonance imaging

Abstract: Abstract. Matching the bolus arrival time (BAT) of the arterial input function (AIF) and tissue residue function (TRF) is necessary for accurate pharmacokinetic (PK) modeling of dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI). We investigated the sensitivity of volume transfer constant (K trans ) and extravascular extracellular volume fraction (v e ) to BAT and compared the results of four automatic BAT measurement methods in characterization of prostate and breast cancers. Variation in delay be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…However, determining the AIF remains technically challenging because of the location of the upstream, slice orientation, partial volume, and flow artifacts. Studies have shown that AIF can have a large effect on the accuracy of computed pharmacokinetic parameters [32][33][34] . Theoretically, a local AIF sampled at the inlet to the target tissue should be selected.…”
Section: Discussionmentioning
confidence: 99%
“…However, determining the AIF remains technically challenging because of the location of the upstream, slice orientation, partial volume, and flow artifacts. Studies have shown that AIF can have a large effect on the accuracy of computed pharmacokinetic parameters [32][33][34] . Theoretically, a local AIF sampled at the inlet to the target tissue should be selected.…”
Section: Discussionmentioning
confidence: 99%
“…; Mehrtash et al. ; Paling et al. )) measures the time delay for arterial blood to travel to the capillaries of the tissue from a major upstream artery, such as the popliteal artery, and directly reflects blood transit velocity and/or the route through upstream arteries and arterioles.…”
Section: Introductionmentioning
confidence: 99%
“…Estimating the time delay between the arrival of the CA in the upstream artery and the tissue of interest accurately is an important step to obtain correct parameters from pharmacokinetic modelling of DCE-MRI data (Mehrtash et al, 2016). One way to reliably obtain the delay is to take the time difference between the estimates of the BATs of the TCC and of the AIF, respectively (Kershaw and Buckley, 2006).…”
Section: Discussionmentioning
confidence: 99%